Good Beginnings: Decolonizing Protocols and Agreements or Mouse Crosses River - Philip Jonah Logan Geller (Percées, 2023)
Mouse tries to cross River. Philip attempts to create theatre in an institutional context. What could go wrong? What could go right? A decolonizing offering in how we enter artistic and collaborative relations. What protocols, practices, and understanding are required to have a good beginning?